2008
DOI: 10.1111/j.1524-4733.2007.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

A Modeled Economic Evaluation Comparing Atomoxetine with Stimulant Therapy in the Treatment of Children with Attention-Deficit/Hyperactivity Disorder in the United Kingdom

Abstract: The economic evaluation showed atomoxetine is an effective alternative across a range of ADHD populations and offers value-for-money in the treatment of ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 28 publications
1
54
0
Order By: Relevance
“…A further review of these 45 published full-text reports excluded 32 conference submissions, abstracts or review articles and 13 full-text studies were included in the final review (figure 1). [53][54][55][56][57][58][59][60][61][62][63][64][65] To facilitate comparisons across studies, costs were reported in the original currency as well as in 2010 US dollars. Costs in non-US currencies were first converted to US dollars in the same year based on the annual exchange rate in that year.…”
Section: Methodsmentioning
confidence: 99%
“…A further review of these 45 published full-text reports excluded 32 conference submissions, abstracts or review articles and 13 full-text studies were included in the final review (figure 1). [53][54][55][56][57][58][59][60][61][62][63][64][65] To facilitate comparisons across studies, costs were reported in the original currency as well as in 2010 US dollars. Costs in non-US currencies were first converted to US dollars in the same year based on the annual exchange rate in that year.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, systemic administration of a selective 5-HT2A receptor antagonist (M100907) had opposite actions, remediating impulsivity in both sham-operated and 5-HT-depleted rats. These contrasting influences of the 5-HT2A and 5-HT2C receptor antagonists were mimicked by infusions of the drugs into the nucleus accumbens, but not the mPFC, in intact animals (Cottrell et al, 2008). However, in variations of the 5-CSRTT, it was possible to detect significant reductions in impulsivity after intra-mPFC infusion of the 5-HT2A receptor antagonist.…”
Section: Pharmacological Differentiation Of Impulsivity and Compulsivmentioning
confidence: 96%
“…Data indicate that impulsivity may derive from one or more distinct neurocognitive mechanisms. These include a tendency to pre-potent motor disinhibition, measured by the stop signal reaction time (SSRT) task (Aron and Poldrack, 2005), mediated in human beings through activation of right inferior frontal (RIF) cortex and its subcortical connections (Rubia et al, 2003) and modulated in rats and human beings by norepinephrine (Chamberlain et al, 2006cCottrell et al, 2008), but not serotonin Chamberlain et al, 2006d). Another aspect involves difficulty in delaying gratification and choosing immediate small rewards despite negative long-term consequences, measured by decision making or gambling tasks such as the Cambridge Gambling Task (CANTAB), mediated through orbitofrontal and related cortical circuitry under probable serotonergic modulation (Rogers et al, 1999b), and subcortical circuitry under joint dopaminergic and serotonergic control (Winstanley et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…We used utilities assessed from parents of ADHD children using standard gamble methods. 20 Values and associated ranges are listed in Table 1. Because the 95% confidence intervals around the published values for different utility states overlap, we required that the utility of successful medication without side effects be higher than medication with side effects, which in turn was higher than the utility of untreated ADHD.…”
Section: Markov Transition Modelmentioning
confidence: 99%
“…19 Of children who respond to medication, some would experience persistent adverse effects such as insomnia, and the remainder would have benefits without adverse effects. 20 The model accounts for the natural process of remission of ADHD from 7 to 25 years of age 21,22 and for medication discontinuation for other reasons. 23 …”
Section: Adhd Treatmentmentioning
confidence: 99%